2015
DOI: 10.3389/fevo.2015.00119
|View full text |Cite
|
Sign up to set email alerts
|

Female song rates in response to simulated intruder are positively related to reproductive success

Abstract: Bird song is well studied in males as a sexually selected behavior. However, although song is also common among females, it is infrequently examined and poorly understood. Research suggests that song is often used as a resource defense behavior and is important in female-female competition for limited resources, e.g., mates and territories. If so, song should be positively related to fitness and related to other resource defense behaviors, but this possibility has rarely been explored. Here we examine fitness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 41 publications
4
32
1
1
Order By: Relevance
“…Like other species with female song, lyrebirds are non-migratory (Price, 2009;Logue and Hall, 2014), and do not experience the seasonal extremes associated with the absence of song in females of northern hemisphere species (Slater and Mann, 2004). Our findings support the idea that complex song by females is more commonly associated with intra-sexual competition for ecological resources than with mate attraction (Cooney and Cockburn, 1995;Hall and Peters, 2008;Illes and Yunes-Jimenez, 2009;Cain et al, 2015, see also Tobias et al, 2012, but contradict suggestions of an association with convergent sex roles (Slater and Mann, 2004). Indeed, our study suggests that elaborate female vocal displays can evolve even in species with strong selection for male extravagance.…”
Section: General Implications For Elaborate Vocalizations In Female Ssupporting
confidence: 76%
See 1 more Smart Citation
“…Like other species with female song, lyrebirds are non-migratory (Price, 2009;Logue and Hall, 2014), and do not experience the seasonal extremes associated with the absence of song in females of northern hemisphere species (Slater and Mann, 2004). Our findings support the idea that complex song by females is more commonly associated with intra-sexual competition for ecological resources than with mate attraction (Cooney and Cockburn, 1995;Hall and Peters, 2008;Illes and Yunes-Jimenez, 2009;Cain et al, 2015, see also Tobias et al, 2012, but contradict suggestions of an association with convergent sex roles (Slater and Mann, 2004). Indeed, our study suggests that elaborate female vocal displays can evolve even in species with strong selection for male extravagance.…”
Section: General Implications For Elaborate Vocalizations In Female Ssupporting
confidence: 76%
“…Identifying the ecological and life-history correlates of female song requires detailed study of song, particularly in species that diverged closest to the ancestral node (Odom et al, 2014). At present, little is known about female song in other early diverging species, with the exception of the Maluridae (Cooney and Cockburn, 1995;Hall and Peters, 2008;ColombelliNégrel et al, 2010;Dowling and Webster, 2013;Cain et al, 2015). Therefore, it is not yet clear what aspects of song in lyrebirds have been retained since their ancestor diverged from the main branch of the oscines, and what features have since evolved.…”
Section: General Implications For Elaborate Vocalizations In Female Smentioning
confidence: 99%
“…This contrasts somewhat with other studies where female territorial defense behavior in response to a simulated female intruder (but not spontaneous song), predicts reproductive success (Cain et al, 2015), and where higher rates of female song at the nest increases predation risk (Kleindorfer et al, 2016). It is known that female song in bellbirds has an important role in female competition (Brunton et al, 2008b) and here we found that higher female song rate during both incubation and chick-rearing were positively correlated with male provisioning rate (Figure 2).…”
Section: Discussioncontrasting
confidence: 99%
“…If characteristics of female song reflect competitive ability, then we predict an association between female song rate and reproductive success and a positive association between aspects of song performance and female fitness. To our knowledge, just one study has examined female song rates and fitness (Cain et al, 2015), and it found a positive relationship between defense responses to song playbacks during territory establishment and the probability of successful nesting. No study has yet examined how female song complexity and song rate during breeding relates to reproductive success.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is growing focus on the occurrence [3] and functions of female song [4], mostly using the perspective of life history and social selection theory. Female song is widespread and ancestral in songbirds, and females sing across 71% of extant species spanning 32 families [5].…”
Section: Introductionmentioning
confidence: 99%